1983
DOI: 10.1115/1.3245620
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Fusion Boundary Energy Transport During Arc Welding

Abstract: An experimental technique is presented to identify fusion boundary (liquid/solid interface) energy transport mechanisms during welding procedures. The gas-tungsten-arc spot-welding procedure, using a low melting point specimen material (lead), was chosen to demonstrate the methods. Vaporization energy losses were found to be important during the growth of the fusion boundary. Significant thermal convection was absent within the weld pool for applied currents less than about 100 A, and for such cases the locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1984
1984
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…For typical DMD materials such as stainless and H13 steels, and at the lower laser intensities used for this process, boiling losses can be considered insigni®cant and only evaporation losses considered [46]. Landram [47] concluded that evaporation losses were more important than convection in determining heat transfer to the melt pool boundary (the fusion zone in welding) and Salcudean et al [48] noted that they are sensitive to the power distribution (the largest loss is caused by a concentrated¯ux acting uniformly). Dykhuizen and Dobranich drew attention to the applicability of this pathway to DMD [15].…”
Section: Energy¯ow From the Melt Poolmentioning
confidence: 99%
“…For typical DMD materials such as stainless and H13 steels, and at the lower laser intensities used for this process, boiling losses can be considered insigni®cant and only evaporation losses considered [46]. Landram [47] concluded that evaporation losses were more important than convection in determining heat transfer to the melt pool boundary (the fusion zone in welding) and Salcudean et al [48] noted that they are sensitive to the power distribution (the largest loss is caused by a concentrated¯ux acting uniformly). Dykhuizen and Dobranich drew attention to the applicability of this pathway to DMD [15].…”
Section: Energy¯ow From the Melt Poolmentioning
confidence: 99%
“…C'est pour une application à la soudure qu'une première étude a été publiée [Landram 1983]. Des expériences en laboratoire, dans lesquelles un courant entre une cathode et une anode a fait fondre un morceau de plomb dans une cavité de nickel en demi-sphère, ont été menées.…”
Section: 51ldentification1dunclassified